Pengaruh Media Sosial Terhadap Perubahan Sosial Di Masyarakat - Lisda Waty Harianja (Jurnal Insan Pendidikan dan Sosial Humaniora, 2024)
Social media serves as a tool that enables individuals to easily interact with each other without the constraints of time, distance, location, or additional costs. Its usage has become a societal necessity, bringing both positive and negative impacts on cultural and social changes. The presence of social media has deeply integrated into modern society, becoming an inseparable element of mass media. Its effects are evident in the transformation of norms, habits, and attitudes gradually eroded by the advancements in mass media, replaced by new patterns of behavior. The ongoing technological advancements, particularly in social media, require attention to ensure that the society does not fall prey to its negative effects.